INFLUENCE OF ORGANISATIONAL STRATEGY ON IMPLEMENTATION OF ELECTRONIC PROJECT MONITORING INFORMATION SYSTEM IN PUBLIC TERTIARY INSTITUTIONS IN KENYA - MBURUGU, Mr. KIREMA NKANATA; MULWA, DR. ANGELINE SABINA; KYALO, DR. DOROTHY NDUNGE. (IJRDO - Journal of Applied Management Science, 2015)
The principal objective of the study reported in this article was to empirically assess on the influenceof organisational strategy on the implementation of Electronic Project Monitoring Information System(e-ProMIS) in Public Tertiary Institutions in Kenya. The population of the study comprised membersof staff from public tertiary institutions in Kenya. A sample of 210 members of staff was selectedusing stratified and simple random sampling techniques. Questionnaire with both open and closedended items with Likert-type interval scale anchored on a five point scale was used to collect data.Descriptive statistics show that majority of the public tertiary institutions in Kenya applied reactorstrategy (M=3.40, SD=1.13) followed by defender strategy (M=2.46, SD=0.56) and a few of themused prospector strategy (M=2.26, SD=0.68). Reactor which was the dominant strategy utilised intertiary institutions is not a stable strategy since institutions that adopt it are not able to respondeffectively to the environment. They adapt only when environmental pressures force them to do so.Results from inferential statistics show that r is equal to 0.513, indicating that organisational strategyhas a moderately strong influence on implementation of e-ProMIS. The value of R squared is 0.263,indicating that organisational strategy explains 26.3% of the variation in the implementation ofelectronic project monitoring information system in public tertiary institutions in Kenya. The βcoefficient of prospector strategy is 0.025, that of defender strategy is 0.397 and reactor strategy is0.217. These results indicate that prospector strategy had no statistically significant influence on theimplementation of e-ProMIS (β=0.025, t=0.280, p=0.780>0.05). Comparing the p values, it can benoted that the p values for defender strategy (p=0.000) and reactor strategy (p=0.003) are bothstatistically significant. The β values imply that one unit change in implementation of e-ProMIS isassociated with 2.5% changes in prospector strategy, 39.7% changes in defender strategy and 21.7%changes in reactor strategy.